Effect of resistance-interval training with two different intensities on cytokeratin18 and some functional parameters in women with fatty liver - Somayeh Rajabi; Roya Askari; Amir Hossein Haghighi; Nasrin Razaviyanzadeh (Mashhad University of Medical Sciences, 2020)
Introduction: Nowadays, noninvasive approaches in the investigation of hepatocyte death and the use of non-pharmacological adjunctive therapies are considered by health professionals. This study was performed with aim to compare the effect of different intensities of combined training on cytokeratin18 )marker of hepatocyte death( and some indicators of physical function in women with Non-alcoholic fatty liver disease. Methods: This applied and semi-experimental study with pre-test and post-test design was performed on 33 women with NAFLD in Shahrood city in 2018. The subjects were randomly divided into training and control groups. Combined training 1 Group performed Aerobic Interval Training (AIT) along with resistance training and combined training 2 group performed High Intensity Interval Training (HIIT) along with resistance training for 12 weeks. Functional tests (Upper and lower strength and endurance, aerobic power) and blood samples were performed before and after 12 weeks of training. Data were analyzed by SPSS software (version 24)  and R statistical software and repeated measures ANOVA tests. PResults: There was significant difference between two training groups in the CK18 level (p<0.001) and combined training 1 group had higher decrease in the CK18 level. Also, both combined training significantly increased upper and lower maximal strength and muscular endurance and VO2max, as well as a significant decrease in body fat percentage (p<0.001). There was no significant difference between groups in weight and BMI (p>0.05). Conclusion: Women with Non-alcoholic fatty liver disease may be able to use both intense and moderate combined training to reduce body fat percentage, improve physical performance indicators independent of weight loss and use moderate intensity combined training as a non-pharmacological adjunctive therapy to prevent cell death.